2010
DOI: 10.1203/pdr.0b013e3181e17caa
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response to Oxygen and Endotoxin in Newborn Rat Lung Ventilated With Low Tidal Volume

Abstract: Herein, we determined the contribution of mechanical ventilation, hyperoxia and inflammation, individually or combined, to the cytokine/chemokine response of the neonatal lung. Eight-dayold rats were ventilated for 8 h with low (ϳ3.5 mL/kg), moderate (ϳ12.5 mL/kg), or high (ϳ25 mL/kg) tidal volumes (V T ) and the cytokine/chemokine response was measured. Next, we tested whether low-V T ventilation with 50% oxygen or a preexisting inflammation induced by lipopolysaccharide (LPS) would modify this response. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 28 publications
4
26
1
Order By: Relevance
“…Indeed, 195 genes showed an altered mRNA expression after LPS, compared to 17 and 11 after additional ventilation and oxygen treatment, respectively. This occurred despite the reduction of the amount of LPS of 33% compared to the dose used in three previous similar studies (4,7,9). This strong effect of LPS is even more astonishing, as these three studies showed that 24 h after the LPS injection (i.e., at the beginning of MV), the proinflammatory cytokine production was almost back to normal and the morphological aspect of the lung was comparable to the CTRL animals.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Indeed, 195 genes showed an altered mRNA expression after LPS, compared to 17 and 11 after additional ventilation and oxygen treatment, respectively. This occurred despite the reduction of the amount of LPS of 33% compared to the dose used in three previous similar studies (4,7,9). This strong effect of LPS is even more astonishing, as these three studies showed that 24 h after the LPS injection (i.e., at the beginning of MV), the proinflammatory cytokine production was almost back to normal and the morphological aspect of the lung was comparable to the CTRL animals.…”
Section: Discussionmentioning
confidence: 80%
“…Thanks to an atraumatic intubation procedure performed under direct laryngoscopy, we were able to wean ventilated newborn rats off anesthesia and MV which allowed us then to perform outcome measurements after a chosen time period of recovery (7). In addition to the transitory increase of proinflammatory cytokines/chemokines measured in different studies immediately after MV and/or hyperoxia exposure in immature lungs (4,8,9), our previous study demonstrated changes in MMP9 and tropoelastin mRNA expression only as a delayed reaction 48 h after the ventilation episode (7). This indicated a second wave of gene regulation that could correspond to mechanisms occurring in premature infants developing BPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in all of them changes in lung molecular biology were noted after a short period of ventilation. In ventilation model of normal newborn rats, using simpler, volume-controlled, time-cycled ventilators, it may 24 or may not 18,25 be pressure-limited. The tidal volume admitted for ventilation ranged from 3.5 to 40 ml/kg, with a volume considered median between 8.5 and 12 ml/kg, and a frequency between 20 and 600 cycles/minute, with the median frequency between 100 and 160 cycles/minute.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…BPD is a consequence of an inflammatory lung injury that leads to remodeling of the developing lung. Inflammation results from a variety of stimuli with mechanical ventilation, hyperoxia, and infection being the most prominent (22,48). The incidence of BPD increases with decreasing gestational age.…”
mentioning
confidence: 99%